Mr. William's Pneumonia - Ernest Talarico; Stephen Michael Koveck (Association of American Medical Colleges, 2012)
Abstract This is a problem-base-learning (PBL), tutorial teaching case intended for 1st-year medical school human gross anatomy during the course of anatomical dissection and discussion sessions with respect to the urinary system. It can also be used for second-, third- and forth-year medical students because of its clinical content. Some adaptation of the case material may be needed, and can be done by faculty to suit the specific medical school audience without diluting the basic science and clinical usefulness of the case. The PBL Group ideally consists of 6 students and 1 faculty tutor. The focus of this case is metastatic renal cell carcinoma with vena caval involvement into the right atrium. The case is divided into 3, 2-hour sessions, where pages are handed-out, one at a time, and discussed by the group; learning issues, hypothesis, tests, etc., are generated. Images are accessed for discussion where indicated within the case and prior to discussion of subsequent pages. The tutor may verbalize the guiding questions located in the Tutor Guide to assist the PBL group in the process of the case. Sessions 2 and 3 begin with a discussion of knowledge obtained via research of learning issues from prior sessions and sharing of knowledge and resource materials. The case ends with students being supplied with case objectives/vocabulary. A tutor guide with guiding questions is available at the rear of this case packet. If the PBL group was successful, each participant will be able to answer the cases objectives, guiding questions, and have mastered the vocabulary. The ultimate goal is not diagnosis, but is the understanding and application of basic sciences (human gross anatomy, histology, embryology and radiology, as well as pathology and some pharmacology) to an actual clinical case designed to reinforce material being learned in laboratory and discussion sessions. This project supports the leaning of basic science and clinical concepts relative to the renal/urinary system through application of self-directed/group learning in a problem-based learning format. The project is adaptable by faculty for use in medical school years one through four, as well as residency. The case focus is that of metastatic renal cell carcinoma, and it incorporates human gross anatomy, histology, embryology, radiology, pathology, as well as elements of pharmacology, oncology and surgery. All the characters within the text and reports are fictional; no identifying information is presented within this case. This case was tested with a group of 26, first-year medical students. All reported that the case was useful to their learning of basic science as applied to a clinical situation. All felt that the learning objectives were clearly stated (at the end of the case), and students felt that objectives were achieved. Some learning issues and guiding questions were suggested, and then incorporated into the Resource & Tutor Guide. Labels were also added to radiograms within the Guide to facilitate understanding by faculty and tutors.